Management Curriculum 2013 in the Framework of Improving the Quality of Education in Islamic Junior High School 2 Ponorogo - Saepul Anwar; M. J. M. Khadafi (Educan : Jurnal Pendidikan Islam, 2020)
Education is one of the main factors in making humans a quality and innovative human being. Because humans are required to always do innovation and renewal and have better knowledge, creativity and life skills. In the field of education, the role of management is very important in determining the quality of an educational institution especially curriculum management. From the above background the authors formulated the title "Management of Curriculum 2013 in the Context of Improving the Quality of Education in Islamic Junior High School 2 Ponorogo". The formulation of the problem in this thesis is: How is curriculum management in Islamic Junior High School  2 Ponorogo and how actions taken by schools in improving the quality of education. Research conducted by researchers is including qualitative descriptive research and in collecting data the author uses interviews, observation and documentation. As for the analysis, the author uses descriptive qualitative analysis techniques, in the form of written or oral data from people and observed behaviors so that in this case the researcher tries to conduct a real research. The results of the research by the author are known that the curriculum in Islamic Junior High School  2 Ponorogo uses the Semester Credit System (SKS), then for the curriculum used is the 2013 curriculum. For curriculum planning there is such a thing as team work in charge of preparing curriculum planning, determining assessments, reports assessment and determine that students deserve to be in the acceleration program or the regular program. For organization, it involves each of the allied teachers under the coordination of the Principal and the Curriculum Section. For implementation, it is divided into two levels, namely the implementation of the school level curriculum and the implementation of the class level curriculum. And lastly there is an evaluation that is by holding a meeting with the deputy head of the curriculum, the evaluation carried out is monitoring. After conducting an evaluation, the next step is to make an evaluation report. Then to support quality improvement in schools, the institution facilitates adequate facilities and infrastructure so that teaching and learning activities can run well, and also opens 3 educational programs, namely a regular program, a bilingual program, and an acceleration program. Various educational service programs are aimed at improving the quality of education in Islamic Junior High School  2 Ponorogo.